As marcas da homofobia na vida de um docente: narrativas que ecoam da sala de aula - Côrtes, Diego Alves (2021)
This research aimed to learn and discuss about heteronormativity in my teaching and personal life. The study is about the trajectory of my life addressing the main formative processes that led me to be the gay math teacher I became. The text brings narratives about the main moments of my life (childhood, adolescence, college, work, study at the University of Brasília, life in the United States and coming back to Brazil) in addition to bringing reports and reflections on homosexuality with the themes family, teaching and religion. I also bring important narrations about the moment when I put a stop to heteronormativity and learned to live my Queer side. The research addresses two themes: homosexuality and teaching. Theoretically, the study "made an alliance with authors" who address the concepts of the issue of gender and homosexuality, bringing important definitions to the topics covered. The methodology used was narrative research which is basically about telling life stories, being a process of telling the lived experiences. This way, stories are relived and recounted, reflecting on the facts that occurred and analyzing the construction of the lived moments. I proposed to narrate all the conflicts created by my homosexuality, the presence of heteronormativity in my life since I was a child and all the challenges and prejudices faced due to my sexual orientation. I also tried to register how my self-acceptance process as a gay took place, in addition to telling the battles I had to fight against homophobia both in the family and at work. When exercising my role as a teacher, I could not disassociate the marks of my sexuality and my gender, even if I tried to hide them. And when these marks overflowed, I suffered homophobia several times, but all the homophobic attacks I suffered throughout my life made me stronger and able to better understand my sexuality. Today I can deal with homophobia with peace of mind, as I know my rights as a homosexual citizen that I am. The whole process of liberation I went through was long and painful, but once I was able to accept myself, I became a much happier and more fulfilled person.